Effect of nocturnal Temperature-controlled Laminar Airflow on the reduction of severe exacerbations in patients with severe allergic asthma: a meta-analysis. Issue 1 (1st January 2021) - Chauhan, A. J.; Brown, T. P.; Storrar, W.; Bjermer, L.; Eriksson, G.; Radner, F.; Peterson, S.; Warner, J. O.
ABSTRACT: Background : Allergen avoidance is important in allergic asthma management. Nocturnal treatment with Temperature-controlled Laminar Airflow (TLA) has been shown to provide a significant reduction in the exposure to allergens in the breathing zone, leading to a long-term reduction in airway inflammation and improvement in Quality of life (QoL). Allergic asthma patients symptomatic on Global Initiative for Asthma (GINA) step 4/5 were found to benefit the most as measured by Asthma Quality of Life Questionnaire (AQLQ). However, the effect of TLA on severe asthma exacerbations is uncertain and therefore a meta-analysis was performed. Methods : Patients with severe allergic asthma (GINA 4/5) were extracted from two 1-year randomised, double-blind, placebo-controlled trials conducted with TLA. A meta-analysis of the effect on severe exacerbations was performed by negative binomial regression in a sequential manner, defined by baseline markers of asthma control (symptoms and QoL scores). Results : The pooled dataset included 364patients. Patients with more symptoms at baseline (ACT<18 or ACQ7>3; N=179), had a significant mean 41% reduction in severe exacerbations (RR=0.59 (0.38-0.90); p=0.015) in favour of TLA. Higher ACQ7 cut-points of 3.5-4.5 resulted in significant reductions of 48-59%.More uncontrolled patients based on AQLQ total and symptom domains ≤3.0 at baseline also showed a significant reduction in severe exacerbations for TLA vs. placebo ((47% (p=0.037) and 53% (p=0.011), respectively). The meta-analysis also confirmed a significant difference in AQLQ-responders ((Minimal Clinically Important Difference)≥0.5; 74% vs. 43%, p=0.04). Conclusion : This meta-analysis of individual patient data shows a beneficial effect on severe exacerbations and quality of life for TLA over placebo in more symptomatic patients with severe allergic asthma. These outcomes support the national management recommendations for patients with symptomatic severe allergic asthma. The actual effect of TLA on severe exacerbations should be confirmed in a prospective study with larger numbers of patients.